Conceptional Model of Regional Agricultural Water Management System - Nagy, Ildikó; Tamás, János (Acta Agraria Debreceniensis, 2005)
Our study focuses on the water management improvement of the Hajdúsági-löszhát (loess ridge). The Hajdúsági-löszhát (loess ridge) is an intensive agricultural area. At the same time, the problem of increasing water demand is still not solved, so towards of safety production irrigation should be improved. To realise this should be known not even agricultural water demands but industrial and urban ones as well, thus a complex water management system is required to be worked out. In the first part of the research, the water demand in the area is mapped, then a conceptional model of the Hajdúsági-löszhát’s (loess ridge’s) water management system is created. After collecting data the water management scenario is summarized in a real time model splitted into five periods. During the research, the instruments of spatial informatics (GIS) are used to get acquainted with the variation of the hydrological parameters in space and time. To understand and simulate the different decision making processes and to choose the right decision alternative, a decision support system is created with the use of spatial informatics data. In addition, considering the potentially right decision alternative, irrigation will be started in practice, an effect and after-effect inquiry will be made, and the results will be analysed, evaluated and summarized. Finally, a suggestion to the most adequate irrigation technology will be made.